The electrochemical potential of a natural green battery from fruits - Mohd Noor, Adibah; Mohamed Khir, Northaqifah Hasna; Kamal Arıfın, Sıtı Aısyah; Md Yasın, Nur Alya Farıza; Mohd Dın, Nurul Adılah; Adam, Zetty Nabılah (2025)
A battery is an electric cell, a device that produces electricity from a chemical reaction used for many purposes. Commercial batteries often contain toxic materials that can contaminate water sources and cause harm to the environment due to improper disposal. As the pollution alarms, this study investigates the potential of fruits as a green alternative to commercial batteries. The objectives of this study are to compare the pH and voltages of variations of fruits, to determine the difference in voltage between fresh fruit, non-fresh fruit and blended fruit and to study the potential of fruits as an alternative to the battery for a decoration product created. The methodology begins with the pH identification of four variations of fruits; lemon, orange, green apple and pineapple. Then, the voltage of the fruits was measured using copper and zinc as electrode. A product decoration in flower form is created with the fruit juice as a green battery. The resulted pH of lemon was measured is 3 and pH 4 is for orange, green apple and pineapple. Fresh fruit juice produced higher voltages than non-fresh and blended samples, with lemon, orange, green apple and pineapple yielding 2.08 V, 1.48 V, 1.76V and 1.22 V, accordingly. Meanwhile, the light-emitting diode (LED) lighted up the brightest when using lemon fruit compared to other fruits. These findings demonstrate that fresh lemon juice is the most effective fruit-based electrolyte for biobattery applications, offering higher voltage output and better performance for powering small decorative devices compared to orange, green apple and pineapple.